A fast knowledge-based plane reconstruction method from noisy 3D point cloud data - Shazmin Aniza, Abdul Shukor; Young, Ken (International Association of Science and Technology for Development (IASTED), 2011)
12th IASTED International Conference on Computer Graphics and Imaging (CGIM 2011) organized by International Association of Science and Technology for Development (IASTED), 16th - 18th February 2011 at Innsbruck, Austria.